Generalized stacking fault energy of carbon-alloyed paramagnetic γ-Fe. (28th December 2018) - Xie, Ruiwen; Li, Wei; Lu, Song; Song, Yan; Vitos, Levente
Abstract: Generalized stacking fault energy (GSFE) is an important parameter for understanding the underlying physics governing the deformation mechanisms in face-centred cubic (fcc) materials. In the present work, we study the long-standing question regarding the influence of C on the GSFE in austenitic steels at paramagnetic state. We calculate the GSFE in both -Fe and Fe–C alloys using the exact muffin-tin orbitals method and the Vienna Ab initio Simulation Package. Our results show that the GSFE is increased by the presence of interstitial C, and the universal scaling law is used to verify the accuracy of the obtained stacking fault energies. The C-driven change of the GSFE is discussed considering the magnetic contributions. The effective energy barriers for stacking fault, twinning and slip formation are employed to disclose the C effect on the deformation modes, and we also demonstrate that the magnetic structures as a function of volume explain the effect of paramagnetism on the C-driven changes of the stacking fault energies as compared to the hypothetical non-magnetic case.